2014
DOI: 10.1177/1357633x14537775
|View full text |Cite
|
Sign up to set email alerts
|

Screening electroencephalograms are feasible in the emergency department

Abstract: We investigated the feasibility and quality of a wireless, four-channel screening electroencephalogram (EEG) device on patients presenting to the emergency department (ED) with a possible seizure disorder. A convenience sample was used of ED patients presenting with a preliminary diagnosis of syncope, potential partial-complex or generalized seizure disorder, head injury with prolonged symptoms or acute undiagnosed altered mental status. Study patients had a screening EEG in the ED, but the emergency physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…They reported that 11% of stat EEGs showed NCSE. With similar findings, Alroughani 5 described a rate of 9% in patients with unknown cause of impaired level of consciousness, and Bastani et al 22 described subclinical epileptiform activity in 12% of patients studied with a screening EEG device in the ED. More recently, Brenner et al 23 found nonconvulsive seizure activity in 8% of patients when comparing a portable six-lead Brainmaster EEG device with conventional EEG.…”
Section: Discussionmentioning
confidence: 58%
“…They reported that 11% of stat EEGs showed NCSE. With similar findings, Alroughani 5 described a rate of 9% in patients with unknown cause of impaired level of consciousness, and Bastani et al 22 described subclinical epileptiform activity in 12% of patients studied with a screening EEG device in the ED. More recently, Brenner et al 23 found nonconvulsive seizure activity in 8% of patients when comparing a portable six-lead Brainmaster EEG device with conventional EEG.…”
Section: Discussionmentioning
confidence: 58%
“…As such, this may represent an opportunity to thoughtfully deploy newly developed rapid-EEG systems that require less local technical knowledge and can be integrated with teleneurology tools for remote emergent interpretation in the acute emergency setting. 3,[6][7][8][9][23][24][25][26] The association between EEG availability, rurality, and hospital transfers echoes earlier studies of rural-to-urban ED transfer for CT imaging. 27,28 These studies of transfers from rural EDs in a single-payer (Canadian) health care system identified lack of CT availability as common, intervenable and possible cost-effective method of decreasing transfers.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, improving access to screening EEG or tele-EEG appears to be a highly actionable area for optimizing triage among nonmetropolitan, low-seizure volume EDs with high transfer rates. 3,6,8,[23][24][25] Importantly, cEEG capability involves not only the availability of equipment and technical expertise but also access to epilepsy providers for EEG interpretation, which may be limited especially in rural areas. As such, this may represent an opportunity to thoughtfully deploy newly developed rapid-EEG systems that require less local technical knowledge and can be integrated with teleneurology tools for remote emergent interpretation in the acute emergency setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple devices have been studied to adapt the traditional EEG infrastructure to more effectively meet the clinical needs of these emergent situations [3][4][5]. Such devices have frequently utilized fewer EEG electrodes to simplify and speed their application to the patient's scalp.…”
Section: Introductionmentioning
confidence: 99%